Impact of Supervised-concurrent Exercise During Pregnancy on Infant Neuromotor Skills: A Post-hoc Analysis Stratified by Maternal BMI - Sandra Sanchez-Parente; Kara Kern; Alex Claiborne; Breanna Wisseman; Dylan Steen; Brittany Roenker; Ashton Lilley; Cody Strom; Edward Newton; James DeVente; Steven Mouro; David Collier; et al. (Sports Medicine - Open)
Abstract Background This is a post-hoc secondary analysis of a randomized controlled trial whose purpose was to analyze the effect of a supervised-combined aerobic and resistance exercise (concurrent exercise) training program during pregnancy on 1-month infant neuromotor skills based on maternal pre-pregnancy body mass index (BMI). Methods Ninety-four pregnant women participated in this study, which was conducted at East Carolina University (Greenville, North Carolina, USA) between 2015 and 2018, and were allocated into concurrent exercise (n = 42) or stretching and breathing group (n = 52). The exercise group followed a 50-min 3 days/week moderate intensity concurrent exercise training program from the 16th gestational week until birth. Infant neuromotor skills were assessed with the Peabody Developmental Motor Scales, 2nd edition (PDMS-2). Results Per protocol analyses showed that infants from the exercise group and whose mothers were normal-weight, had higher PDMS-2 Stationary, Locomotion (borderline) and Gross Motor Quotient (GMQ) percentiles than infants of stretching and breathing participants (p = 0.022, ηp2 = 0.20; p = 0.054, ηp2 = 0.15; p = 0.022, ηp2 = 0.20, respectively). No differences between groups were found in infants whose mothers were normal-weight in reflexes percentiles in the adjusted model, or those infants whose mothers were overweight/obese in any of the outcomes (all p ≥ 0.05). Conclusions Concurrent exercise training during pregnancy improves neuromotor skills in infants at 1 month of age in normal-weight women. Further studies are needed to understand the influence of concurrent exercise training during pregnancy on infants whose mothers are overweight or obese, and the potential mechanism behind the role of maternal BMI in the development of infant neuromotor skills. Clinical Trial Registration ClinicalTrials.gov Identifier: NCT03838146.